INVENTARISASI HAMA TANAMAN JATI UNGGUL NUSANTARA DI KEBUN PERCOBAAN UNIVERSITAS NUSA BANGSA COGREG, BOGOR - Napitu, Beni; Bintani, Kustin Meiganati; Pandjaitan, Poltak BP (Jurnal Nusa Sylva, 2012)
Identity development is done in Excel Nusantara University Experimental Station and Nation village in monoculture planting Cogrek with a wide scale, but often face exploitation teak plantations by the pest problem which is one of the impact of the production quality. Therefore this research needs to be done by identifying pests in the village JUN cogrek.This study aims to determine the types of pests or signs of gelaja attacks, the number of trees affected and the intensity of the damage was found in teak (Tectona grandis Lf) plantations in the village in Cogrek. The sampling done by making extensive plot with size 0.1 ha (20 mx 50 m) with a sampling intensity of 10% of the crop stand and trubusan Teak (Tectona grandis Lf) by means of systematic random sampling. Measured parameter type and pests that attack stands trubusan Teak, intensity of damage by pests and the number of trees attacked.The results showed that the types of pests that are found in plant stands about 7 species, whereas in plants trubusan about 8 types of pests are found. For the number of trees attacked by as many as 101 trees on the plant stand while the number of trees that were attacked on 88 trubusan plant trees and intensity of pest damage on trubusan averaged amounted to 11.8% leaves and stems are attacked 0.7%. All the results of the intensity calculations pest damage can be categorized mild attack.